STRATEGI PENGENDALIAN PERSEDIAAN STOK OBAT PROGRAM RUJUK BALIK PASIEN BPJS DI KLINIK ZHAFIR PALEMBANG - Dale Anggara; Erliany Syaodih; Kahar Mulyani (Bajang Institute, 2025)
There are several critical issues in managing the inventory of drugs for the Referral Program (PRB) at the Zhafir Clinic in Palembang. Internal audit data from the clinic shows that during the period January-December 2023, there was a stockout of PRB drugs of 27% of the total demand, with an average stockout duration of 3-5 days per incident. This condition resulted in 42% of PRB patients having to receive alternative drugs that did not match the initial prescription from the specialist doctor. This study aims to identify and analyze the Inventory Control Strategy for the BPJS Referral Program Drug Stock at the Zhafir Clinic in Palembang. The research method is a qualitative descriptive study, with a case study approach. The results of the study show that the just in time strategy in managing the inventory of drugs for the Referral Program (PRB) at the Zhafir Clinic in Palembang can reduce or even eliminate unnecessary inventory. Therefore, the clinic does not store large quantities of drugs in the warehouse. That way, storage costs can be minimized and warehouse space can be optimized for other needs. Just in time strategy can reduce waste, such as inventory excess (excess inventory), waiting time (waiting time), and defects (expired drugs).